Notary’s Obligations to Prevent Suspicious Financial Transactions in Money Laundering Crimes - Dhia Savira Fadhilla; Mohammad Arief Amrullah; Ainul Azizah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Notaries dom’t have guidelines and guidance to prevent the occurrence of money laundering crimes that are faced with various types and characteristics of their opponents. The ambiguity of the norms in Article 16 paragraph (1) letter a of the Notary Law should be able to state the obligations of Notaries in carrying out their duties, must act in a trustworthy, honest, fair, independent, impartial manner and protect the interests of the parties involved in legal acts. This type of research is normative juridical using 3 (three) types of approaches, namely the statutory approach, the conceptual approach and the comparative approach. Based on the results of the study, it can be concluded that Notaries are required to apply the Principle of Recognizing Service Users (PMPJ) as part of implementing the principle of prudence, at least including identification of Service Users, verification of Service Users and monitoring of Service User transactions. This application applies to Notaries in providing services when preparing and conducting transactions for the benefit of or for and on behalf of Service Users, regarding the purchase and sale of property, management of money, securities, and/or other financial service products, management of checking accounts, savings accounts, deposit accounts, and/or securities accounts, operation and management of companies and/or establishment, purchase, sale of legal entities. Notaries can implement applications such as Data Banks for their parties who will create PPJB Deeds and Powers of Attorney for Sale and Purchase that are in accordance with KTP and KK, so as to minimize the occurrence of money laundering. Especially related to land, the land ownership limit must not exceed 20 hectares + 5 hectares.